(untitled) (Historias, 2004)
Miguel Hidalgo y Costilla has been one of the major characters in Mexican historiography. Known as Padre de la Patria since the Grito de Dolores, he became the central figure of the dominant discourse of national unity. This created a myth which obstacled the investigations on his real character and impact on Mexican history. In 1953, the celebration of his bicentennial promoted a renewed historiographical interest in Hidalgo which produced a more balanced approach to the subject by stripping the man from the myth and offering a different view from the surrounding events of the Hidalgo revolt. This has encouraged research producing new interpretations of the process of Mexican independence. This article aims at offering an analysis of the more recent historiographical approaches to the Hidalgo figure in Mexican history.